Target Tirpitz X-craft, agents and dambusters : the epic quest to destroy Hitler's mightiest warship - Bishop, Patrick (HarperPress, 2012)
Tirpitz was the pride of Hitler's navy, the most powerful battleship in Europe. To Churchill she was "The Beast", a menace to Britain¡s supply lines. An "Iron Castle" that could withstand any bomb or torpedo. She haunted the imaginations of the men directing Britain's war. Plan after plan was hatched to send her to the bottom. But in the end it was Bomber Command who finished her off. In 1944, Wing Commander James "Willie" Tait, led Lancasters from 617 Squadron - the famous "Dambusters" - and 9 Squadron on a series of raids which ended with the destruction of Hitler's Tirpitz.